Degradation of trace contaminants using coupled sonochemistry and Fenton's reagent - Jiang, Y (Water science and technology : a journal of the International Association on Water Pollution Research, 2003)
The degradations of phenol in air-equilibrated aqueous media were investigated using coupled sonochemistry and Fenton's reagent for a variety of operating conditions. The decomposition yields of phenol (100-500 microM) were substantially enhanced due to the addition of Fenton's reagent (FeSO4 into the solutions irradiated at 608 kHz with 30 W and with reaction temperature 25 +/- 1 degree C. The decomposition process follows a pseudo-first-order reaction kinetics with respect to phenol concentration, and the rate constant of phenol disappearance observed increases by approximately 2-3 fold when FeSO4 was between 400 and 1000 M at pH = 3.5 +/- 0.2 (controlled by phosphate buffer) as a result of Fe(II) reaction with H2O2 enabling further production of additional OH* radicals. The results obtained here also indicate that the decomposition rate of aqueous phenol using coupled ultrasound and Fenton's reagent was strongly dependant on the initial concentration of reactant, the amount of Fe(II) added as well as the pH of solution. The optimal operating conditions for 100-500 microM phenol decomposition in the air-equilibrated aqueous media were obtained when FeSO4 concentration was between 400 and 1,000 microM with pH in the range 3.5-4.2 under ultrasonic irradiation at 608 kHz, 30 W and reaction temperature 25 +/- 1 degree C